Natural hydrogen emanations in Namibia: Field acquisition and vegetation indexes from multispectral satellite image analysis. (5th October 2022) - Moretti, Isabelle; Geymond, Ugo; Pasquet, Gabriel; Aimar, Leo; Rabaute, Alain
Abstract: Natural hydrogen exploration is now active in various places of the world. Onshore, correlation between natural H2 generation and the presence of iron rich rocks especially from Archean and Neoproterozoic cratons have been observed. Emanations and accumulations of H2 have already been confirmed in such geological settings in Australia, South Africa and Brazil. The geological similitude and the presence of numerous sub circular depressions that are a good proxy for hydrogen emanations suggest that hydrogen resources may also exist in Namibia. We present here the results of a data acquisition campaign which allowed us to confirm the presence of natural hydrogen in this country in the vicinity of Neoproterozoic Banded Iron Formation. The H2 content in the soil, as in Brazil, is variable within the depressions in time and space and is particularly time sensitive across the day. Comparison of the H2 signal versus time within these two regions shows a similar behavior of the soils with an increase of the H2 flow at the middle of the day. In addition, these new data allow us to better constrain the morphological characteristics of such H2 -emiting depressions. By using satellite images and digital elevation model we propose a new proxy to differentiate potentially H2 -emiting features from other type of depressions such as Salt Pan. The Landsat multispectral images and their processing through NDVI and SAVI indexes, that highlight a ring of healthy vegetation around the sub circular area with scarce vegetation already observed appear able to discriminate between H2 emitting structures and other soft depressions. Highlights: Natural hydrogen resource exists in Namibia. Emanations of H2 are systematic in the SCD in the Okakarara area. The amount of H2 in the soil varies across the day as in Brazil. Vegetations indexes, SAVI and NDVI, allow discriminating H2 emitting structures. A halo of dense vegetation exists around the H2 emitting structures.